2016
DOI: 10.1136/neurintsurg-2015-012147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dural venous sinus stenosis and hypoplasia in a generalized population

Abstract: The prevalence of bilateral transverse sinus stenosis in the general population is not trivial. These data may be used as a reference for understanding the mechanistic role of stenoses in idiopathic intracranial hypertension, tinnitus, and refractory headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 22 publications
5
73
1
2
Order By: Relevance
“…Durst et al found the prevalence of unilateral transverse sinus stenosis or hypoplasia in the normal population to be 33% and the prevalence of bilateral transverse sinus stenosis to be 5% 25. Radvany et al observed in a study of 12 patients that two patients who underwent catheter venography had no pressure gradient, despite apparent transverse sinus stenosis on CTV 26.…”
Section: Recommendationsmentioning
confidence: 99%
“…Durst et al found the prevalence of unilateral transverse sinus stenosis or hypoplasia in the normal population to be 33% and the prevalence of bilateral transverse sinus stenosis to be 5% 25. Radvany et al observed in a study of 12 patients that two patients who underwent catheter venography had no pressure gradient, despite apparent transverse sinus stenosis on CTV 26.…”
Section: Recommendationsmentioning
confidence: 99%
“…Several open and endovascular interventions have even been developed to treat anomalies of the CVOT (Ahmed et al, 2011; Eisenman, 2011; Houdart et al, 2000; Starke et al, 2015). However, anatomic variance is quite wide and lumenal irregularities such as sinus stenosis may not always be pathologic (Durst et al, 2016). Figure 1 shows the structure of the CVOT anatomy within the head.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the pathophysiological relationship between dural venous sinus stenosis and hydrocephalus remains incomplete as such stenosis is also found in 31–39% of patients without IIH,24 25 including 15.9% of those with headache and normal ICP 26. Despite incomplete understanding of the relationship between dural venous sinus stenosis and hydrocephalus, the final common pathway of elevated venous sinus pressures and increased ICP does not appear to be limited to patients with IIH, though correcting venous outflow obstruction may not be enough to effectively treat patients with congenital hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%